Postoperative Harris Hip Score Versus Harris Hip Score Difference in Hip Replacement: What to Report? - Nikolai Ramadanov; Maximilian Voss; Robert Hable; Hassan Tarek Hakam; Robert Prill; Mikhail Salzmann; Dobromir Dimitrov; Roland Becker (Orthopaedic Surgery)
ABSTRACT Background Reliable scientific information is crucial for assessing hip function and evaluating the success of hip surgery. The Harris Hip Score (HHS) is the most widely used tool for measuring hip function and, in particular, the outcomes of hip surgery. The aim of this study was to conduct a systematic review of the literature to identify randomized controlled trials (RCTs) that reported the HHS for hip replacement treatment groups and to test whether there was a substantial difference between reporting only the postoperative HHS or the HHS difference (HHSdiff). Methods PubMed, CNKI, and Epistemonikos were searched until March 1, 2024. The risk of bias, level of evidence, and publication bias were assessed. As HHS is a continuous outcome, mean difference (MD) with 95% confidence intervals (CIs) was calculated using the Hartung–Knapp–Sidik–Jonkman method and a common‐effect/random‐effects model. The same approach was used for both postoperative HHS and HHSdiff. The effect of the two treatment groups studied (minimally invasive vs. conventional approach) on postoperative HHS was then compared with the effect of the two groups studied on the difference in HHS. Results A total of 41 RCTs, involving 3572 patients, with a low to high risk of bias and a low to moderate publication bias were included. The measured outcome parameters showed a low to moderate level of evidence. There was no relevant difference in the reporting of HHS only postoperatively or HHSdiff when comparing two hip replacement treatment groups in RCTs, measured at 0–0.5, 3, 6, and 12 months postoperatively. Conclusion The present study showed that there is no relevant difference between reporting of the HHS only postoperatively or HHSdiff when comparing two hip replacement treatment groups in RCTs. Both methods of HHS reporting produced comparable results in an identical cohort of 3765 patients undergoing hip replacement surgery.